Tocqueville, democracy, and religion: checks and balances for democratic souls - Kahan, Alan S. (Oxford University Press, 2015)
A ground-breaking study of the views of the greatest theorist of democracy writing about one of our most pressing issues. Alan S. Kahan, a leading Tocqueville scholar, shows how Tocqueville's analysis of religion is simultaneously deeply rooted in his thoughts on nineteenth-century France and America and pertinent to us today--